The Social Psychology of Racially Biased Policing: Evidence-Based Policy Responses. (October 2020) - Kahn, Kimberly Barsamian; Martin, Karin D.
Police killings of unarmed African Americans, such as George Floyd in 2020, continue to cause nationwide protests and calls for change. Psychological science knows much about biased policing and can inform policy to promote equitable policing. Social psychology's extensive findings on stereotyping, attitudes, and intergroup relations help clarify the role of officer racial bias. This article reviews implicit and explicit bias, race-crime stereotypes, intragroup bias, ingroup favoritism, stereotype threat, and dehumanization in policing interactions, all of which can lead to racially disparate use of force. Based on this science, some policy responses can mitigate bias: Officer level de-biasing training, body-worn cameras, automatic license plate readers, and federal policing reform legislation are discussed. The lack of a coordinated, national effort to collect and analyze police use of force data undermines tracking fatal incidents and bias therein, which are therefore harder to remediate.